The acdS Gene Expression of Rhizobacteria Isolated from Rhizospheric Soil of Pineapple under Stressful Condition - Dori Kusuma Jaya; Sri Ismiani; Zaitun Ritaqwin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The unfavorable rhizosphere environment for the growth of rhizobacteria and plants such as flooding and herbicide is relatively common for these rhizobacteria to express the acdS gene which encodes ACC deaminase. This study aims to observe the expression of the acdS gene in the rhizobacterial isolates from pineapple plants affected by the environmental stressors. The expression of the acdS gene was observed by growing the bacterial isolate on a Dworkin-Foster medium containing 3 mM.L-1 ACC and observing the RNA abundance of the isolate based on the Cq value in the RT-qPCR reaction. The selected bacterial isolates were then identified molecularly using the 16S rDNA gene. This study showed that 2 out of 7 bacterial isolates growing on a DF+ACC medium were selected for the RT-qPCR process. The two isolates came from flooding and herbicide stressors with Cq values ​​of 17.86 and 20.87, respectively. The two isolates were 1F and 2H which were identified molecularly as Burkholderia sp. and Pseudomonas psychotolerans in which both genera of bacteria commonly have the acdS gene. The two isolates can be used as inoculant candidates in the production of biological organic fertilizers as well as in their empowerment through land use management practices to help plants tolerate environmental stressors and promote plant growth.